Acute toxicity and behavioural responses of a freshwater mussel Lamellidens marginalis (Lamarck) to dimethoate exposure - Kumar, Saurabh; Pandey, Rakesh Kumar; Das, Shobha; Das, Vijai Krishna (Recent Research in Science and Technology, 2013)
Dimethoate is a commonly used organophosphate pesticide (OP) in agricultural practices, from where they reach into natural freshwater bodies through surface run-off, affecting the life of non-target aquatic organisms. Molluscs accumulate contaminants in their body tissues and thus are used as bio-indicator for evaluating water quality and habitat degradation. The mussels have great economic value, since they are consumed as food and have therapeutic significance. In this study 96h static acute toxicity test was carried out for dimethoate in freshwater mussel, Lamellidens marginalis. The mussels were exposed to 8 different concentrations of dimethoate (35.00, 37.00, 39.00, 41.00, 43.00, 45.00, 47.00, and 49.00 mg L-1) and control (00.00 mg L-1). The mortality data were subjected to EPA Probit analysis (version 1.5) statistical software based on Finney’s method. The 24, 48, 72 and 96h LC50 values of dimethoate for freshwater mussel were determined as 45.09, 40.52, 38.71 and 36.35 mg L-1 respectively. Mussels show behavioural responses during exposure by exhibiting increase in duration for shell closure, increase in mucus secretion and decrease in oxygen consumption.